Virtual Algorithm Simulation (VAS) Based on Problem: Learning Media in Medical Surgical Nursing - Nurul Hikmatul Qowi; Trijati Puspita Lestari; Siti Sholikhah (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2019)
Introduction: Innovative learning media for online simulation-based nursing students is still not optimal. The study aimed to develop online simulation video-based learning media, namely virtual algorithm simulation (VAS) based on problems in medical-surgical nursing (MSN). Methods: A research development or Research and Development (R&D) which consists of two stages. The first phase of the study was conducted focus group discussion (FGD) with eight medical surgical nursing lecturers and expert discussion with 50 students, three of IT experts, and two MSN experts. The second phase of the research was conducted FGD with five participants, and socialization of instructional media to six lecturers and 54 students. The feasibility test instrument uses learning media assessment instruments consisting of subcategories of learning media rules, Computer Assisted Interaction (CAI), management, and the relevance of the material and syllabus. Data were analyzed using descriptive analysis. Results: The assessment of media experts showed the highest mean in the VAS management subcategory of 3.53. Evaluation of nursing experts and students with the highest mean in the subcategory of material relevance and syllabus, namely 3.9 and 3.57. The results of discussions with experts stated that 100% of the learning media Virtual Algorithm Simulation (VAS) is suitable for use as a medium for learning medical surgical nursing. Conclusions: VAS can be used as a learning media for medical surgical nursing. Online simulation-based learning media can facilitate the accessibility of learning material, increase knowledge and skills of nursing students.